2013
DOI: 10.3389/fcimb.2013.00105
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal epithelial cell apoptosis and loss of barrier function in the setting of altered microbiota with enteral nutrient deprivation

Abstract: Total parenteral nutrition (TPN), a commonly used treatment for patients who cannot receive enteral nutrition, is associated with significant septic complications due in part to a loss of epithelial barrier function (EBF). While the underlying mechanisms of TPN-related epithelial changes are poorly understood, a mouse model of TPN-dependence has helped identify several contributing factors. Enteral deprivation leads to a shift in intestinal microbiota to predominantly Gram-negative Proteobacteria. This is asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
64
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 65 publications
2
64
0
1
Order By: Relevance
“…A lthough total parenteral nutrition (TPN) is an essential therapy for patients who cannot tolerate enteral nutrition, there are numerous and significant clinical sequelae associated with TPN treatment (1). These clinical complications, which include altered immunological responses, hepatic dysfunction, metabolic derangements, endotoxemia, bacterial infections, and sepsis, can delay or make it difficult to wean patients back onto enteral nutrition.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A lthough total parenteral nutrition (TPN) is an essential therapy for patients who cannot tolerate enteral nutrition, there are numerous and significant clinical sequelae associated with TPN treatment (1). These clinical complications, which include altered immunological responses, hepatic dysfunction, metabolic derangements, endotoxemia, bacterial infections, and sepsis, can delay or make it difficult to wean patients back onto enteral nutrition.…”
mentioning
confidence: 99%
“…These clinical complications, which include altered immunological responses, hepatic dysfunction, metabolic derangements, endotoxemia, bacterial infections, and sepsis, can delay or make it difficult to wean patients back onto enteral nutrition. Several studies have indicated that early TPN administration in critically ill patients is associated with worsened clinical outcomes and increased rates of septicemia, often from enterically derived organisms (1,2). These issues clearly highlight that a more detailed understanding of the underlying mechanisms of TPN-related intestinal complications is needed both to improve the selection and administration of TPN to patients and for the development of new therapeutic options for patients dependent on TPN.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The apoptosis-associated uncoupling of bone formation and resorption in osteomyelitis is reviewed in Marriott (2013). The intestinal epithelial cell apoptosis in the setting of altered microbiota with enteral nutrient deprivation is reviewed in Demehri et al (2013).…”
mentioning
confidence: 99%
“…The paper (Demehri et al, 2013) in this issue introduces a shift in our understanding of intestinal microbiota such as Gram-negative Proteobacteria after enteral nutrient deprivation. The altered microbiota setting leads to increased intestinal proinflammatory cytokines, decreased epithelial cell proliferation, and increased epithelial cell apoptosis.…”
mentioning
confidence: 99%